2006
DOI: 10.1091/mbc.e05-12-1183
|View full text |Cite
|
Sign up to set email alerts
|

Myristoylated, Alanine-rich C-Kinase Substrate Phosphorylation Regulates Growth Cone Adhesion and Pathfinding

Abstract: Repellents evoke growth cone turning by eliciting asymmetric, localized loss of actin cytoskeleton together with changes in substratum attachment. We have demonstrated that semaphorin-3A (Sema3A)-induced growth cone detachment and collapse require eicosanoid-mediated activation of protein kinase C (PKC) and that the major PKC target is the myristoylated, alanine-rich C-kinase substrate (MARCKS). Here, we show that PKC activation is necessary for growth cone turning and that MARCKS, while at the membrane, coloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
74
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(79 citation statements)
references
References 62 publications
4
74
1
Order By: Relevance
“…They demonstrate that nonphosphorylated MARCKS is membrane associated, and that phosphorylation triggers its translocation into the cytosol. MARCKS needs to move, in PKC-dependent manner, between membrane and cytosol to promote adhesion (Gatlin et al, 2006;Kim et al, 1994;McLaughlin and Aderem, 1995;Rombouts et al, 2008). Our microscopic and biochemical observations suggest that eicosanoidinduced detachment of dynamic adhesions is paralleled by PKC activation, MARCKS phosphorylation and dissociation of MARCKS-P from the plasma membrane.…”
Section: Pkc Activation and Cell Detachmentmentioning
confidence: 67%
See 1 more Smart Citation
“…They demonstrate that nonphosphorylated MARCKS is membrane associated, and that phosphorylation triggers its translocation into the cytosol. MARCKS needs to move, in PKC-dependent manner, between membrane and cytosol to promote adhesion (Gatlin et al, 2006;Kim et al, 1994;McLaughlin and Aderem, 1995;Rombouts et al, 2008). Our microscopic and biochemical observations suggest that eicosanoidinduced detachment of dynamic adhesions is paralleled by PKC activation, MARCKS phosphorylation and dissociation of MARCKS-P from the plasma membrane.…”
Section: Pkc Activation and Cell Detachmentmentioning
confidence: 67%
“…Previous studies have shown that some adhesions are sensitive to the intracellular messenger 12(S)-hydroxyeicosatetraenoic acid [12(S)-HETE] (Gatlin et al, 2006;Szekeres et al, 2002;Tang et al, 1995). To test the effect of this eicosanoid on cell adhesion, we exposed individual cultured cells (WM-1617) to gradients of 12(S)-HETE (pipette tip located 100 μm away, near the upper left hand corner in Fig.…”
mentioning
confidence: 99%
“…In addition, MARCKS is involved in cell adhesion, lamellipodia formation, initiation of neuritogenesis, neurite outgrowth, growth cone adhesion, pathfinding, dendrite branching, dendritic spine morphogenesis, and synaptic plasticity (13,28,39,41,(61)(62)(63)(64)(65)(66)(67)(68)(69)(70)(71). Knockdown of MARCKS by RNA interference and overexpression of MARCKS mutants revealed that non-phosphorylated MARCKS stabilizes growth cone adhesion, enhances branching and growth of dendrites, elongates dendritic spines, and enhances initiation of neuritogenesis and neurite outgrowth (65,66,68,69).…”
Section: Discussionmentioning
confidence: 99%
“…Cell attachment can result from the stabilization of integrin-mediated adhesions controlled by non-pMARCKS. (35) We then sought to clarify whether the PKC-mediated phosphorylation of MARCKS is necessary for the induction of cell motility or invasion induced by TPA stimulation. When MARCKS mRNA was suppressed in the presence of TPA, cell motility and invasion were significantly reduced in comparison to the control cells.…”
Section: Discussionmentioning
confidence: 99%